PHARMACOLOGICAL RESTRAINT OF RED-FOOTED TORTOISES USING COMBINATIONS OF KETAMINE, MIDAZOLAM AND BUTORPHANOL - Raposo Monteiro, Eduardo; de Faria da Silva, Eduardo Lázaro; Dias Pestana Santos, Maria Guadalupe; Rossi Júnior, João Luiz; Dias Ferreira Júnior, Paulo (Revista Acadêmica Ciência Animal, 2011)
The present study tested the association of ketamine, midazolam and butorphanol on the pharmacological restraintof red-footed tortoises. Eight animals were used, which were submitted to three different intramuscular treatments every 15 days: ketamine 30 mg/kg (C); ketamine 30 mg/kg + midazolam 1 mg/kg (CM) e ketamine 30 mg/kg + butorphanol 1 mg/kg (CB). The variables evaluated were: period of restraint, degree of analgesia and muscle relaxation, skin temperature and recovery time. There were no significant differences among treatments for the onset of anesthesia and the degree of muscle relaxation. None of the treatments provided surgical anesthesia. Recovery was prolonged in treatments using CM and CB. However, only the CM treatment differed significantly (p < 0.05) in comparison to treatment C. The temperature did not change over 60 minutes for all treatments. Under the conditions of this study, the combination of midazolam or butorphanol did not result in better analgesia and muscle relaxation of red-footed tortoises, and it prolonged their recovery period.